Spermatogonia and spermatocyte ultrastructure in Hoplias malabaricus (Teleostei, Characiformes : Erythrinidae) - Negrao, JNC; de Carvalho, E. D.; Foresti, F.; Quagio-Grassiotto, I (Cambridge University Press, 2002)
The Hoplias malabaricus primary spermatogonium shows a large nucleus, central nucleolus, and low electron-dense cytoplasm containing nuages. In cysts, they undergo several mitotic divisions with incomplete cytokinesis, giving rise to secondary spermatogonia. These are smaller than the primary spermatogonia and their nuclei have one or two eccentric nucleoli. Spermatocytes I can be identified by the presence of synaptonemal complexes. Spermatocytes II are smaller than spermatocytes 1, displaying roughly compacted chromatin. All these cell types remain interconnected by thick-walled intercellular bridges, which have membranous reinforcements during mitosis and meiosis. These cell types show a well-developed endomembranous system, one of the centrioles anchored to the plasma membrane and small nuages. Their mitochondria are large and circular, with few cristae. In the last generations of spermatogonia, the mitochondria are smaller, elongate and have more cristae. In the spermatocytes, the mitochondria are small and round. Similarities found in relation to germ cells of other teleosts are discussed.
Keywords: ultrastructure; spermatogenesis; fish; Teleostei; Characiformes; Hoplias malabaricus